Ultrafast transient optical studies of charge pair generation and recombination in poly-3-hexylthiophene(P3ht):[6,6]phenyl C61 butyric methyl acid ester (PCBM) blend films - Kirkpatrick, James; Keivanidis, Panagiotis E.; Bruno, Annalisa; Ma, Fei; Haque, Saif A; Yarstev, Arkady; Sundstrom, Villy; Nelson, Jenny (My University, 2011)
Charge generation and recombination are studied in blend films of poly-3-hexylthiophene (P3HT) and [6,6']phenyl C61 butyric acid methyl ester (PCBM) using ultrafast transient absorption spectroscopy. We find that the charge generation yield depends upon both blend film composition and thermal annealing. The data suggest that recombination occurs over a wide range of time scales and that, in the least favorable cases, the fastest charge recombination occurs on a time scale similar to exciton diffusion. The results are explained using a simple model that incorporates the effect of P3HT domain size on exciton diffusion and uses empirical models of recombination kinetics. We propose our method as a route to interpretation of spectroscopic data where different processes occur on similar time scales.
Keywords: Excitons; Diffusion; Organic polymers; Kinetics; Recombination